PERILAKU LANSIA DALAM PENGOBATAN RHEUMATOID ARTHRITIS (REMATIK) DI KELURAHAN PANGKALAN KASAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU TAHUN 2017 - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2018)
Rheumatoid Arthritis (Arthritis) is a degenerative joint disease. One class of rheumatic diseases that often accompany old age. Behavioral treatments are the efforts taken to obtain the treatment in order to cure the disease being suffered. This research is aimed at the extent to which the elderly behavior in the treatment of Rheumatoid Arthritis (rheumatism) in sub- district pangkalan kasai of seberida district of Indragiri Hulu in 2017. This research is a qualitative research with in-depth interviews on the research subjects namely 10 major informants, 10 people supporting informants, and informants Key 2 people. There are 5 variables: knowledge, attitude, culture (customs), access to health services and family support. The result of this research concludes that the behavior of elderly is still not good, because the informant knowledge is still lack of it because of the indifferent informant attitude toward the health service so that lead to the search of own treatment by using herbs based on the cultural influence of the elderly who still used in medicine From generation to generation. So the family supports the elderly to conduct their own treatment because the treatment is done safer.